2015
DOI: 10.1016/j.fob.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of BAMLET complexes is due to oleic acid and independent of the α‐lactalbumin component

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
3
25
1
4
Order By: Relevance
“…However, opposing views on specificity and cytotoxicity of HAMLET/BAMLET (the bovine counterpart) can be found in the literature. For example, while even recent papers still suggest that HAMLET/BAMLET are specifically cytotoxic to cancer cells [13,14], our results demonstrated that BAMLET could kill cancer cells (HeLa and A-549 lines) and normal cells (ChoK-1 and NIH-3T3 lines) almost with the same strength [15] and confirmed the results of Brinkmann on BAMLET cytotoxicity to non-cancer derived primary cells [16]. Similarly, several works established that HAMLET/BAMLET components (α-LA and OA) alone were unable to kill cancer cells [17,18] highlighting the importance of the synergy of the components in the tumor toxicity.…”
Section: Introductioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However, opposing views on specificity and cytotoxicity of HAMLET/BAMLET (the bovine counterpart) can be found in the literature. For example, while even recent papers still suggest that HAMLET/BAMLET are specifically cytotoxic to cancer cells [13,14], our results demonstrated that BAMLET could kill cancer cells (HeLa and A-549 lines) and normal cells (ChoK-1 and NIH-3T3 lines) almost with the same strength [15] and confirmed the results of Brinkmann on BAMLET cytotoxicity to non-cancer derived primary cells [16]. Similarly, several works established that HAMLET/BAMLET components (α-LA and OA) alone were unable to kill cancer cells [17,18] highlighting the importance of the synergy of the components in the tumor toxicity.…”
Section: Introductioncontrasting
confidence: 43%
“…However, other articles pointed out that OA prepared without the protein is sufficient for the potent cytotoxicity [20,21]. We demonstrated that the isolated FA OA and the polyunsaturated linoleic acid induced caspase-independent cell death at the same concentration at which BAMLET does [15]. It has also been shown that mono-and polyunsaturated FAs could be internalized by receptor-mediated endocytosis or by diffusion across the cell membranes [22,23] and influenced inflammation, apoptosis, and growth inhibition processes [24,25].…”
Section: Introductionmentioning
confidence: 66%
“…However, although HAMLET-like compounds have been assayed on 50 different cancer cell lines, the literature contains only 11 types of primary cell cultures, and thus it remains to be seen whether these trends will hold when more types of primary cells are investigated. The 6 immortalised non-cancer cells lines investigated have sensitivities to HAMLET that are in the same range as the cancer cell lines (7,14,16,22). It is not yet clear whether this is due to a general toxicity of HAMLET to healthy cells, or whether HAMLET is targeting a fundamental cancer-like characteristic that is possessed by immortalised non-cancer cell lines.…”
Section: Cytotoxicity To Cancer and Non-cancer Cellsmentioning
confidence: 99%
“…Modelling of SAXS data at pH 9.0 and RP-HPLC measurements give diameters of 1.8 to 3.6 nm depending on the BAMLET preparation method and diameters of 1.8 to 2.8 nm for HAMLET-like compounds made from β-lactoglobulin, lysozyme, parvalbumin, ovalbumin, albumin or immunoglobulin G (5). In filtered water, BAMLET has diameters ranging from 227 to 292 nm, as measured by DLS, depending on the BAMLET preparation method (22). Figure 3 shows a plausible model for a BAMLET oligomer at physiological pH.…”
Section: Partially Unfoldedmentioning
confidence: 99%
See 1 more Smart Citation